جمعية العلماء المسلمين الجزائريين وقضايا المغرب العربي 1931 / 1956 - زيدان هنية; د/علاق محمد (جامعة عمار ثليجي الاغواط, 2023)
الملخص : تناولتهذهالدراسةجمعيةالعلماءالمسلميينالجزائريينوقضاياالمغربالعربي (تونس،ليبيا،المغربالأقصى ) بين 1931و1956م،فكانتجمعيةالعلماءترىضرورةالمساهمةبحسبإمكانياتهافيالنضالالمغاربي،رافضةالسياسةالإستعمارية،وذلكمنخلالغرسفكرةالتحرروالاستقلالوالدفاععنكافةأقطارالمغربالعربي،والوقوفصفاواحدافيوجعالاستعمارومخططاتهالراميةلتفكيكوحدةالمغربالعربيومحوهويتهوامتدادهالتاريخيوالحضاري،فناضلتالجمعيةمعمعالقضاياالتيشهدتهاأقطارالمغربالعربي،خصوصاماتعلقبالممارساتالاستعماريةفيتونستقسيمليبياومسألةنفيمحمدالخامسبالمغربالأقصىفهميتؤكدالبعدالمغاربيفينضالالجمعيةواحساسهابالمصيرالمشتركالذييربطبينكلأبناءالمغربيالعربي . الكلماتالمفتاحية : جمعيةالعلماءالمسلميينالجزائريين،قضاياالمغربالعربي،تونس،ليبيا،المغربالأقصى،وحدةالمغربالعربي،النضالضدالتواجدالاستعماري،التحرر. Summary : This study dealt with the Association of Algerian Muslim Scholars and the issues of the Arab Maghreb (Tunisia, Libya, and Al-Maghreb Al-Aqsa) between 1931 and 1956 AD. Standing together in the pain of colonialism and its plans aimed at dismantling the unity of the Arab Maghreb, its essentiality, and its historical and civilizational extension. The common destiny that binds all the people of the Arab Maghreb.